Die karitative Tätigkeit der traditionellen christlichen Kirchen in Ungarn während des Kommunismus und ihre Wirkung auf die kirchliche Wohltätigkeit im Postkommunismus - Teil 2 - Török, Péter; Nagy, István; Joób, Máté (European Journal of Mental Health, 2010)
Charitable Activities of Historical Christian Churches in Hungary during Communism, and their Effects on Post-Communist Charitable Church Activities; Part 2: In addition to assessing charitable activities of historical Christian churches in Hungary during Communism from a fact-finding, descriptive angle, this two-part study also provides a view of what effects these have had on post-Communist charitable church activities. Understandably, this necessitates a brief overview of the types and volume of charitable activities carried out by the Catholic, Reformed and Lutheran churches prior to the Communist power grab. In the years following the Second World War, the majority of church-run social institutions came under State control. The new employees often looked upon the tasks they were to carry out only as a way of making a living, and they lacked a commitment to the service they were to perform. The way in which State Socialist politics strove to use charity and the diaconate in their efforts was aimed at exhausting church and faith, and can be clearly observed. The measures, according to which practically only those institutions where missionary work was impossible (or possible only to a minor degree) could remain in church hands, also served this end. Church leaders who tried to ensure survival by adhering to the official line, also partly became partners to the state. It was considered a step forward when badly paid positions that required hard work and commitment at State-run social institutions were filled by qualified, able labour based on church recommendations and nominations. During the period of dictatorship, charitable activities by congregations and parishes also experienced a strong setback. Following the collapse of Communism, all three churches displayed the intention of reviving their charitable activities by maintaining spirituality and charisma despite a necessary institutionalisation process and strict professionalism. The analysis also pinpoints some cases that highlight the pitfalls of relations with the post-Communist state. The first half of the study presented the operation of helping services linked to Protestant churches, with the Reformed and Evangelical churches discussed separately. The second part provides an overview of the conditions of Catholic charity during the years of dictatorship, using similar considerations, and also takes a look at the times before the Second World War and the changed circumstances following the fall of Communism in 1989.